The Effect of Word Mapping Technique in Teaching Vocabulary - Sonata, Pita; Fauzi, Iwan; Saman, Tampung N (Pusat Kajian Bahasa Daerah & Budaya, 2024)
In teaching vocabulary, the Word Mapping technique is considered the one of appropriate and applicable techniques used by the teacher in the classroom, particularly in building up a large store of words in order to arrange a sentence. The objective of this study is to find out the significant effect of teaching vocabulary by using the word mapping technique. This study used a pre-experimental design where researchers only used one sample to be treated with the teaching using word mapping technique. The pretest and posttest were given before and after treatment made. The data were collected using tests where the scores of the tests were analyzed using paired-sample t-test computation. Then the result showed that teaching vocabulary using word mapping technique is effective to enhance students’ mastery of English vocabulary.